Diary of a Wimpy Kid Hard luck - Kinney, Jeff (London Puffin, 2013)
Greg Heffley$1 (Bs on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg$1 (Bs life destined to be just another hard-luck story?s
English Stories
For children aged 11 - 15 years
Keywords: English stories